Accountability de organizações do espaço público não-estatal: uma apreciação crítica da regulação brasileira - Larroudé, Elisa Rodrigues Alves (2006)
This dissertation examines private nonprofit organizations operating in the public sphere and their accountability relationships with the State and with other societal actors, with the purpose of evaluating the regulatory needs and possibilities for the accountability of such organizations in Brazil. Drawing on international academic and normative parameters, the research seeks to assess to what degree Brazilian regulation of private nonprofit organizations operating in the public sphere ensures ― and what is needed for it to ensure ― the accountability of such organizations before the State and society, indicating the main merits and shortcomings of the corresponding regulatory apparatus and presenting possibilities for its improvement. This analysis highlights that while such organizations have numerous duties of demonstrating their anagerial and financial rectitude and the activities they carry out, they have very little obligation to validate that any intended results have been achieved. Furthermore, one realizes that the State has ample power to monitor such organizations and apply sanctions thereto, but society as a whole has considerably less opportunities to demand their accountability. This reveals the importance of such organizations broadening their duties of transparency and of ensuring the prevalence of public interest, so as to ensure to any citizen the prerogative of monitoring private nonprofit organizations operating in the public sphere.